Current state of stock and fishery of red king crab Paralithodes camtschaticus at West Kamchatka - P. Yu. Ivanov (Известия ТИНРО)
Current state of the red king crab population at West Kamchatka is considered on the data of bottom trawl surveys and fishery statistics since 2013. Some biological parameters of the crabs and assessments of the commercial stock are presented; recent condition of the red king crab fishery and evaluation of the total allowable catch are discussed. The red king crab fishery was resumed in 2013, after 8 years of ban caused by the population decrease. During the ban, the stock restored and exceeded the value observed before the ban: the total accounted abundance of red king crab in 2017 was about 244 . 106 ind. that was the highest level for the last two decades, with the number of commercial males estimated as 110 . 106 ind. — this amount was never observed before on the shelf of western Kamchatka, at least in four decades of surveys. Recently the northern forbidden district and Khayryuzovsky district of the shelf zone lost their role of the main areas of crabs reproduction and their juveniles feeding, in favour to the Ichinsky district located southward. Recent fishery of red king crab is fruitful and sustainable. In the last 3 years, the major part of annual catch is transported alive to ports of China and South Korea. For this purpose, the caught crabs are sorted strictly aboard fishing vessels and the largest males are released back to the sea. Possibly, year-to-year increasing of the males size on the West Kamchatka shelf is caused by this sorting and releasing; another effect of the large-sized crabs releasing is relatively low number of recruits in the last couple of years. The fishery elimination coefficient is estimated in the range 5–16 % of the total accounted stock for 2013–2019, that shows a highly precautionary approach. Gradual decreasing of the crab commercial stock is forecasted for the nearest future, though the stock will remain above the target value. Current state of the red king crab population at West Kamchatka is not considered as dangerous, and ongoing intense fishery of this valuable species within the recommended volumes will not affect this sustainable state.